Evaluación de la posición y la orientación del hueso hioides en las diferentes maloclusiones (2022)
Objective: To compare the position of the hyoid bone in relation to class I, II and III skeletal malocclusions by means of the cephalometric tracing of the hyoid triangle proposed by Dr. Mariano Rocabado. Method: 154 digital lateral cephalic cephalic radiographs were analyzed, obtained from patients who entered the orthodontic clinic of the Antonio Nariño University, Circasia branch, corresponding to individuals of both sexes. The radiographs were analyzed using the Facad DEMO version software, where the vertical, horizontal and rotational position of the hyoid bone was determined utilizing of the cephalometric tracing of the hyoid triangle proposed by Mariano Rocabado.